2015
DOI: 10.1002/jhm.2422
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalist attitudes toward the assessment and management of dyspnea in patients with acute cardiopulmonary diseases

Abstract: Background Dyspnea is a common symptom in patients hospitalized with acute cardiopulmonary diseases. Routine assessment of dyspnea severity is recommended by clinical guidelines based on the evidence that patients are not treated consistently for dyspnea relief. Objective To evaluate attitudes and beliefs of hospitalists regarding the assessment and management of dyspnea. Design Cross-sectional survey Settings Nine hospitals in the United States. Measurements Survey questions assessed the following dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…A survey of hospitalists, regarding only patients admitted for acute cardiopulmonary disease, suggested that the addition of dyspnea assessment would “have a significant effect on existing nursing and physician workflows” [4]. However, our data show the majority of clinical nurses readily adopted routine dyspnea measurement on all patients, finding it easy to incorporate the new documentation into their workflow.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…A survey of hospitalists, regarding only patients admitted for acute cardiopulmonary disease, suggested that the addition of dyspnea assessment would “have a significant effect on existing nursing and physician workflows” [4]. However, our data show the majority of clinical nurses readily adopted routine dyspnea measurement on all patients, finding it easy to incorporate the new documentation into their workflow.…”
Section: Discussionmentioning
confidence: 87%
“…Routine pain assessment and documentation is nearly universal; dyspnea assessment is not. Barriers to routine dyspnea documentation include concerns that it will have a deleterious effect on nursing workflow and that it will not be readily accepted by nurses [4]. The present study addresses these concerns.…”
Section: Introductionmentioning
confidence: 98%
“…In a recent study that evaluated the attitudes and beliefs of hospitalists regarding the assessment and management of dyspnea, we found that most hospitalists indicated that awareness of dyspnea severity influences their decision for treatment, diagnostic testing, and timing of the discharge. Moreover, whereas less than half of the respondents reported experience with standardized assessment of dyspnea severity, most stated that such data would be very useful in their practice …”
Section: Discussionmentioning
confidence: 99%
“…Attitudes were examined using questions modified from a previous survey of health professional attitudes toward assessment and management of breathlessness [26] (used and modified with permission from the authors). While the original survey assessed hospital doctors' attitudes toward dyspnoea assessment and management in patients with acute cardiopulmonary diseases [26], in our study modifications were made to align the questionnaire wording with our focus on chronic breathlessness. For example, an original survey statement was: "The patient's experience of dyspnea should be used to guide treatment decisions independent of objective measures such as respiratory rate and oxygen saturation".…”
Section: Questionnairesmentioning
confidence: 99%
“…In contrast, there is relatively little is known about clinician attitudes, understanding and confidence in chronic breathlessness assessment and management. Recent surveys of medical professionals concerning dyspnoea reflect positive perceptions of the value of standardised assessments in patient care (n = 255 hospital doctors [23]), but less consistent agreement about the ability of patients to rate their dyspnoea on a scale (42% [26]). A survey of respiratory and palliative care doctors in Australia and New Zealand also found that a minority reported using a breathlessness scale in clinical practice (30 and 18% for respiratory and palliative care respectively) [22].…”
Section: Gaps In Baseline Confidence Familiarity With and Attitudes mentioning
confidence: 99%